Fostering Sincere Attitudes In Infaq And Charity According To Islamic Education - Ananda Sholih Nasution; Dewi Aryanti (LECTURES: Journal of Islamic and Education Studies, 2023)
In everyday life, the sincere attitude whichis highly recommended in Islamic education is still not well developed in every Muslim. This can be seen in the dailylife of Muslims, such as infaq and alms that are still acking. This isdue to the lack of sincerity in human character. The type of research used in this research islibrary research whichis a type of objective research, the data sources are books (documents) that are commonly used in research, and the data iscollected through a literature review. Here the author finds the result of cultivating a sincere attitude in Islamic education, whichcan be achieved by: equippinge very Muslim with religious education, instilling faith in the soul of every Muslim, and fearing Allah at alltimes, and choosing friends. Carry out activities to instill faith in Muslims in the majesty of Allah SWT and the majesty of His punishment, increase the remembrance of death. And the cultivation of this sincere attitude willmake us alwayswilling to carry out useful activities such as infaq and alms. Because true happinessis not when were ceive but when we can sincerely give to others just because of Allah SWT.